2020
DOI: 10.1080/16583655.2020.1790928
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and hepatoprotective potentials of curcuminoid isolates from turmeric (Curcuma longa) rhizome on CCl4-induced hepatic damage in Wistar rats

Abstract: The present study examined the protective effects of curcuminoid isolates from Curcuma longa against carbon tetrachloride (CCL 4 )-induced hepatic injury in rats. The hepatoprotective effect of the crude extract (150, 300 and 600 mg/kg bw) and curcuminoids (75, 150 and 300 mg bw) was evident by significant increases in the serum antioxidative defence capacities (super oxide dismutase, reduced glutathione, catalase) and reduction in biomarker enzymes of liver integrity (aspartate transaminase, alanine transamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 35 publications
5
27
0
1
Order By: Relevance
“…Oxidative stress and an imbalance between the generation of prooxidant and antioxidant systems have been associated with several organ abnormalities [65][66][67] and implicated in ischemia-reperfusion-induced testicular impairments [44]. The increased ROS generation leads to oxidative stress and activates apoptosis and increased DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and an imbalance between the generation of prooxidant and antioxidant systems have been associated with several organ abnormalities [65][66][67] and implicated in ischemia-reperfusion-induced testicular impairments [44]. The increased ROS generation leads to oxidative stress and activates apoptosis and increased DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Turmeric is used as a blood purifier and used in the prevention and treatment of skin diseases ( Ahmed et al., 2020 ). It was found that the main functions of Curcuma rhizome were hepatoprotective ( Sadashiva et al., 2019 ; Ibrahim et al., 2020 ), anti-inflammatory ( Tejada et al., 2016 ; Xiang et al., 2017 ), antimicrobial ( Singh et al., 2017 ; Ilangovan et al., 2018 ), antiviral ( Alsamydai and Jaber, 2018 ), antifungal ( Hu et al., 2017 ), wound healing ( Tejada et al., 2016 ), antitumour ( Shakeri et al., 2019 ), antivenom ( Sani et al., 2019 ), and immunomodulator ( Mehala and Moorthy, 2008 ). The results revealed the therapeutic potential of C. longa crude extracts, including polysaccharides and curcuminoids as a supportive supplement for cancer patients whose immune systems were crushed during chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, is a polyphenolic natural compound isolated from Curcuma longa, a reputable medicinal plants commonly known as turmeric [13]. Curcumin has been reported for several therapeutic activities against a number of diseases; including antioxidants, hepato-protective [14], anti-inflammatory and anticancer activities. Several literatures have emphasized the anti-antineoplastic properties of curcumin against experimental cell line and chemically induced carcinogenesis in animal models of cancer [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%